A secondary battery

CN123018352APending Publication Date: 2026-10-30JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312263.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,在长循环使用过程中,三元材料体系电池的膨胀力增长较为显著

Benefits of technology

[0004]为了解决现有技术中的技术问题,本申请提供一种二次电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a secondary battery. The secondary battery comprises a shell and an electric core arranged in the shell, the electric core comprising a positive electrode sheet, a negative electrode sheet and a separator; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer comprising graphite, and the orientation index of the graphite being denoted as OI; a functional coating is arranged on the surface of the separator, the thickness of the functional coating being denoted as H (μm); the functional coating comprises a functional material, the elastic modulus of the functional material being greater than or equal to 10 MPa, and the liquid absorption ratio of the functional material being greater than or equal to 3.5; along the thickness direction of the shell, the difference between the inner wall spacing of the shell and the thickness of the electric core is denoted as PM (μm); OI, H and PM satisfy the following relationship: H >= (a*OI)*(b*PM) / 400. The secondary battery of the application matches the thickness of the functional coating with the orientation index of the graphite and the expandable space inside the electric core, so that the functional coating maintains sufficient pore structure and electrolyte supply in the pressure state, effectively inhibits the cycle diving caused by the extrusion of the electrolyte, and delays the capacity attenuation of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a secondary battery. Background Technology

[0002] With the booming development of the new energy vehicle industry, the market is placing increasingly higher demands on the energy density, rate performance, and cycle life of power batteries. Lithium-ion batteries, with their high energy density, excellent rate performance, and environmental friendliness, have become the preferred power source for electric vehicles. Battery cycle life directly determines the vehicle's warranty capability and user experience, and is one of the key indicators for the large-scale promotion of electric vehicles.

[0003] Ternary lithium-ion batteries are widely used in high-end electric vehicle power batteries due to their high specific capacity and operating voltage. However, during long-term cycle use, the expansion force of ternary lithium-ion batteries increases significantly. As the number of cycles increases, the negative electrode graphite material undergoes volume expansion and contraction due to the repeated insertion and extraction of lithium ions. This periodic volume change accumulates continuously inside the cell, causing the overall cell thickness to rebound, which in turn generates continuously increasing compressive force on the internal casing. As the cycle continues, the internal expansion force of the cell gradually increases. As the separator, as a porous insulating layer between the positive and negative electrodes, easily loses the electrolyte it adsorbs and retains under the pressure, leading to uneven electrolyte distribution at the separator-electrode interface and obstruction of ion transport channels. Ultimately, this causes rapid capacity decay, commonly known as the "diving" phenomenon. Summary of the Invention

[0004] In order to solve the technical problems in the prior art, this application provides a secondary battery.

[0005] In the first aspect, this application provides a secondary battery, which adopts the following technical solution: A secondary battery includes a casing and a battery cell disposed within the casing. The battery cell includes a positive electrode, a negative electrode, and a separator. The negative electrode includes a negative current collector and a negative active material layer. The negative active material layer includes a negative active material, which is graphite, and the orientation index of the graphite is denoted as OI. A functional coating is disposed on at least one surface of the separator along its thickness direction. The thickness of the functional coating is denoted as H μm. The functional coating includes a functional material with an elastic modulus ≥10 MPa and a liquid absorption ratio ≥3.5. The difference between the inner wall spacing of the casing and the thickness of the battery cell along the thickness direction of the casing is denoted as PM. μm; the OI, the H, and the PM satisfy the following relationship: H≥(a×OI)×(b×PM) / 400; where a is the first influence factor and b is the second influence factor; the value range of a is 2.3≤a≤2.5 and the value range of b is 3.2≤b≤3.6.

[0006] The secondary battery provided in this application has a functional coating on the surface of the separator. The functional material in the coating has an elastic modulus of ≥10MPa and a liquid absorption ratio of ≥3.5. During battery cycling, it can resist the extrusion pressure generated by the expansion of the negative electrode with sufficient rigidity, maintaining the separator pore structure from being compressed and collapsed. It can also adsorb and retain a sufficient amount of electrolyte, continuously supplying electrolyte when the separator pores are under pressure, thereby effectively suppressing cycle drops caused by electrolyte extrusion. The elastic modulus and liquid absorption ratio of the functional material itself determine the rigidity and liquid retention capacity of the coating per unit thickness, while the thickness of the functional coating determines the total space for this capacity. The two work together to determine the actual pressure resistance and liquid retention effect of the coating. Based on this, this application further correlates the functional coating thickness H with the graphite orientation index OI and the expandable space PM inside the cell using the formula H≥(a×OI)×(b×PM) / 400. This ensures that the functional coating thickness is sufficient to resist the extrusion force generated by the expansion of the negative electrode during cycling, so that the functional coating can still maintain rigidity under the huge expansion force in the later stage of cycling, preventing the electrolyte from being squeezed out. This effectively improves the problem of electrolyte being squeezed out due to the expansion force squeezing the separator in the later stage of cycling of lithium-ion secondary batteries.

[0007] When the functional coating thickness H < (a×OI)×(b×PM) / 400, it means that under the current expansion degree of the negative electrode and the internal space conditions of the cell, the functional coating thickness is insufficient to provide the minimum rigid support and electrolyte retention required to resist the expansion force. At this time, even if the functional material itself has a sufficiently high elastic modulus and liquid absorption ratio, due to the insufficient thickness of the functional coating, the pore structure it can maintain and the total amount of electrolyte it retains after being compressed cannot meet the ion transport requirements of the cycle. The electrolyte in the separator will still be squeezed out under the expansion force, eventually leading to a cycle failure.

[0008] Preferably, the OI, the H, and the PM satisfy at least one of the following conditions: (1) the value of the OI is 0.3-0.7; (2) the value of the H is 2.5-5.0; (3) the value of the PM is 100-500.

[0009] Preferably, the functional material includes at least one of polyacrylamide (PAM), polyvinyl alcohol (PVA), polyoxyethylene (PEO), and polyacrylic acid (PAA).

[0010] Preferably, the functional coating further includes a first binder, which includes at least one of polyvinylidene fluoride (PVDF), polyoxyalkyleneamine (POA), and polymethyl methacrylate (PMMA).

[0011] Preferably, the mass ratio of the functional material to the first adhesive is (80-95):(0.1-1).

[0012] Preferably, the functional coating is disposed on the surface of the separator near the negative electrode sheet.

[0013] Preferably, the median particle size Dv50 of the graphite is between 10000nm and 13000nm.

[0014] Preferably, the compaction density of the negative electrode active material layer is 1.5-1.65 g / cm³. 3 .

[0015] Preferably, the porosity of the negative electrode active material layer is 25%-40%.

[0016] Preferably, the negative electrode active material layer further includes a second binder, the second binder including at least one of styrene-butadiene rubber (SBR), acrylonitrile multi-element copolymer (LA133), and polyacrylic acid (PAA); the mass ratio of the negative electrode active material to the second binder is (96%-98%):(0.8%-1.5%). Detailed Implementation

[0017] To better understand and implement this application, the technical solution will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some of the embodiments of this application, and not all of them.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.

[0019] Unless otherwise stated, all numerical values ​​for the amounts of expressed components, reaction conditions, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values ​​that can be varied to obtain the desired performance.

[0020] Unless otherwise stated, the terms “a,” “an,” “an,” and “the” as used in this specification are intended to include “at least one” or “one or more.” For example, “a component” refers to one or more components, and therefore more than one component may be considered and may be employed or used in the implementation of the described embodiments.

[0021] The word “and / or” as used in this article refers to one or all of the elements mentioned.

[0022] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] The first aspect of this application provides a secondary battery, including a casing and a cell disposed within the casing. The cell includes a positive electrode, a negative electrode, and a separator. The negative electrode includes a negative current collector and a negative active material layer. The negative active material layer includes a negative active material, which includes graphite, and the orientation index of the graphite is denoted as OI. A functional coating is disposed on at least one surface of the separator along its thickness direction. The thickness of the functional coating is denoted as H μm. The functional coating includes a functional material, the elastic modulus of which is ≥10 MPa, and the liquid absorption ratio of which is ≥3.5. The difference between the inner wall spacing of the casing and the thickness of the cell along the thickness direction of the casing is denoted as PM. μm; the OI, the H, and the PM satisfy the following relationship: H≥(a×OI)×(b×PM) / 400; where a is the first influence factor and b is the second influence factor; the value range of a is 2.3≤a≤2.5 and the value range of b is 3.2≤b≤3.6.

[0025] For example, the elastic modulus of the functional material is any value among 10MPa, 10.5MPa, 11MPa, 11.5MPa, 13MPa, and 15MPa, or any value within the range of any two of the above values; the liquid absorption ratio of the functional material is any value among 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, and 4.5, or any value within the range of any two of the above values; the value of 'a' is any value among 2.3, 2.4, and 2.5, or any value within the range of any two of the above values; the value of 'b' is any value among 3.2, 3.3, 3.4, 3.5, and 3.6, or any value within the range of any two of the above values.

[0026] In one embodiment of this application, the orientation index OI of the graphite is a dimensionless parameter characterizing the degree of orientation of the graphite crystal in the electrode sheet. Its physical meaning is the ratio of the diffraction peak area of ​​the (002) crystal plane to that of the (004) crystal plane of the graphite crystal.

[0027] In one embodiment of this application, PM = the inner wall spacing of the casing - the thickness of the battery cell, in μm; this solution is particularly applicable to prismatic lithium batteries. When there is only one battery cell, the thickness of the battery cell is the dimension of that single battery cell along its own thickness direction; when there are multiple battery cells, the thickness of the battery cell is the sum of the thicknesses of all the battery cells in the casing along the battery cell stacking direction. The inner wall spacing of the casing refers to the distance between two opposite inner walls of the casing along the battery cell stacking direction.

[0028] In one embodiment of this application, 'a' is a first influencing factor, whose physical meaning is related to the interlayer distance μ (in nm) of the graphite and the graphitization degree G (dimensionless) of the negative electrode material; specifically, a = 0.9G / μ, and the value of G is 80%-90%. For example, the value of G is any value among 80%, 83%, 85%, 87%, and 90%, or any value within the range of any two of the above values. The diffraction angle 2θ of the (002) crystal plane is obtained by X-ray diffraction, and the interlayer distance d is calculated by substituting it into Bragg's formula. (002) That is, μ, with units of nm; d (002) Substituting into Franklin's formula, the degree of graphitization is calculated.

[0029] In one embodiment of this application, b is a second influencing factor, the physical meaning of which is related to the median particle size Dv50 (in nm) of the graphite; specifically, b = Dv50 / 3500.

[0030] In one embodiment of this application, the OI, the H, and the PM satisfy at least one of the following conditions: (1) the OI is 0.3-0.7; (2) the H is 2.5-5.0; (3) the PM is 100-500. For example, the OI value is any one of 0.3, 0.4, 0.5, 0.6, 0.7 or any value within the range of any two of the above values; the H value is any one of 2.5, 3, 3.5, 4, 4.5, 5 or any value within the range of any two of the above values; the PM value is any one of 100, 200, 300, 400, 500 or any value within the range of any two of the above values.

[0031] The optimal ranges for the graphite orientation index (OI), functional coating thickness (H), and internal expandable space (PM) of the battery cell were further defined. These three parameters are not independent optimization terms, but rather core variables that jointly participate in formula matching. Any deviation of any parameter from its optimal range will lead to a decrease in matching accuracy. OI, H, and PM together determine whether the functional coating thickness can achieve a precise match with the negative electrode expansion degree and the internal space of the battery cell. When OI, H, and PM all fall within their respective optimal ranges, the negative electrode expansion potential reflected by OI is at a reasonable level, the physical containment space reflected by PM is within a moderate range, and H responds precisely based on the above two parameters. The three parameters work together to optimize the correspondence between the calculated value on the right side of the formula and the actual thickness of the functional coating. The functional coating will not be unable to withstand the expansion force due to insufficient thickness, nor will it affect electrode adhesion and ion transport due to excessive thickness. When any parameter deviates from its optimal range, even if the functional coating thickness H still satisfies the formula, its matching accuracy will be affected, and the rigid support and electrolyte retention effect of the functional coating during long-term cycling cannot be maintained at an optimal level. Therefore, the above three preferred ranges together define the optimal working range of each parameter in the formula, which further improves the matching accuracy between the functional coating thickness, the degree of negative electrode expansion, and the internal space of the cell. The rigid support of the functional coating and the electrolyte retention effect are more stable and durable in long-term cycling, and the cycle life and structural stability of the battery are further improved.

[0032] In one embodiment of this application, the functional material includes at least one of polyacrylamide (PAM), polyvinyl alcohol (PVA), polyethylene oxide (PEO), and polyacrylic acid (PAA).

[0033] In one embodiment of this application, the functional material includes polyvinyl alcohol (PVA).

[0034] Functional materials are the core components that enable functional coatings to achieve rigid support and electrolyte adsorption and retention. Their inherent properties directly determine the elastic modulus and liquid absorption ratio of the functional coating. Polyacrylamide, polyvinyl alcohol, polyoxyethylene, and polyacrylic acid are all polymers containing polar groups. The polar groups on their molecular chains have a strong affinity for carbonate electrolytes, which is beneficial for the wetting and retention of the electrolyte in the functional coating. At the same time, their molecular chains form a relatively compact aggregated structure through interactions such as hydrogen bonding, giving the material high intrinsic rigidity. Among the above materials, polyvinyl alcohol has a high degree of molecular chain regularity and stronger interchain hydrogen bonding, which enables it to form a more compact aggregated structure, providing a high liquid absorption ratio while exhibiting superior mechanical rigidity and structural stability.

[0035] In one embodiment of this application, the functional coating further includes a first adhesive, which includes at least one of polyvinylidene fluoride (PVDF), polyoxyalkyleneamine (POA), and polymethyl methacrylate (PMMA).

[0036] The functional materials in the functional coating need to be fixed to the surface of the membrane substrate by an adhesive. Polyvinylidene fluoride, polyoxyalkyleneamine and polymethyl methacrylate all have good adhesion to the membrane substrate and have excellent chemical stability and dimensional stability in the electrolyte environment. They can firmly anchor the functional material particles to the membrane surface and ensure that the functional coating maintains its structural integrity during long-term cycling.

[0037] In one embodiment of this application, the mass ratio of the functional material to the first adhesive is (80-95):(0.1-1). Exemplarily, the mass ratio of the functional material to the first adhesive is any one of 80:1, 90:1, 95:1, 80:0.5, 80:0.1, 90:0.1, 95:0.1, or any ratio within the range formed by any pairwise ratios mentioned above.

[0038] The ratio of functional materials to binders determines the spatial distribution of the functional and binder phases within the functional coating. This application controls the mass ratio of functional materials to the first binder within the aforementioned range. Under this ratio, the functional materials, as the main component of the functional coating, dominate, fully utilizing their functions in rigid support and electrolyte retention. An appropriate amount of binder is uniformly distributed between the functional material particles and between the functional materials and the membrane substrate, forming a continuous bonding network that firmly anchors the functional material particles to the membrane surface and maintains a tight, integrated structure within the functional coating. Through the synergistic optimization of the types of functional materials, binders, and their ratios, the functional coating achieves superior structural stability, rigid support capability, and electrolyte retention capacity, which is beneficial for further improving the battery's cycle life.

[0039] In one embodiment of this application, the functional coating is disposed on the surface of the separator near the negative electrode sheet.

[0040] In some embodiments of this application, a functional coating is disposed on the surface of the separator near the negative electrode. During cycling, the negative electrode graphite material undergoes volume expansion due to the repeated insertion and extraction of lithium ions, which is the main source of expansion force within the cell. Since the expansion force is transmitted outward from the surface of the negative electrode, the side of the separator near the negative electrode is the area most directly and intensely subjected to compression. Therefore, the functional coating bears the greatest actual compressive force on this side, and its actual compression deformation is also the most significant. The functional coating thickness H, defined by the formula H≥(a×OI)×(b×PM) / 400, is the minimum thickness value required to resist this compressive force, calculated based on the degree of negative electrode expansion (OI) and the expandable space (PM) within the cell. By disposing the functional coating on the surface of the separator near the negative electrode, this thickness-defined functional coating first bears the compression at the beginning of the expansion force transmission path, providing rigid support and electrolyte retention at the most critical position with minimal material usage. Compared to placing the functional coating on the side of the separator away from the negative electrode, placing it on the side closer to the negative electrode can more efficiently utilize the thickness of the functional coating to resist expansion forces and avoid deformation of the separator substrate due to an excessively long force transmission path. Compared to placing functional coatings of the same thickness on both sides of the separator, placing them only on the negative electrode side can reduce the amount of functional coating material used without weakening the anti-drain effect, thereby reducing the manufacturing cost and impedance of the battery.

[0041] In one embodiment of this application, the median particle size Dv50 of the graphite is 10000nm-13000nm.

[0042] The particle size of graphite directly affects the packing state and pore structure of the negative electrode active material layer. When the Dv50 of graphite is within the aforementioned range, the packing density between graphite particles is moderate, which can form reasonable interparticle porosity to facilitate electrolyte wetting and lithium-ion transport, while also ensuring a sufficient number of contact points between particles. This avoids excessive interparticle voids due to excessively large particle size, which would affect the liquid absorption and replenishment effect of the functional coating. Simultaneously, graphite particles within the aforementioned particle size range can form a relatively ideal orientation distribution during coating and rolling processes. The expansion degree of the negative electrode during cycling is moderate, avoiding excessively rapid expansion force due to excessively high OI values, and also preventing poor electrode adhesion due to excessively low OI values. This ensures that the matching relationship between H and OI in the weighted formula 1 can stably achieve its intended function. If Dv50 is too large, the gaps between particles increase, and the electrolyte adsorbed by the functional coating is more likely to leak into the electrode, weakening the electrolyte retention effect of the functional coating on the separator side. If Dv50 is too small, the orientation of graphite particles is enhanced, the expansion force increases faster, and the thickness H of the functional coating needs to be increased accordingly to meet the formula requirements, which increases the cell impedance and manufacturing cost.

[0043] In one embodiment of this application, the compaction density of the negative electrode active material layer is 1.5-1.65 g / cm³. 3 .

[0044] Compaction density reflects the degree of packing of graphite particles in the electrode, and its value directly affects the pore structure of the electrode and the orientation of the graphite particles. When the compaction density is within the above range, the negative electrode active material layer has a moderate packing density. On the one hand, this ensures that the graphite particles form a proper orientation during the rolling process, avoiding excessive orientation of graphite particles, increased OI value, and excessively rapid expansion force due to over-compaction. On the other hand, it maintains sufficient internal pores in the electrode, providing ample storage space for the electrolyte, allowing the electrolyte adsorbed by the functional coating to form an effective liquid phase connection with the electrolyte inside the electrode, ensuring rapid transport of lithium ions at the interface.

[0045] In one embodiment of this application, the porosity of the negative electrode active material layer is 25%-40%.

[0046] In some embodiments of this application, the porosity of the negative electrode active material layer is further defined. Porosity reflects the proportion of pores within the negative electrode active material layer to the total volume, which determines the upper limit of the electrolyte volume that the electrode can accommodate and the migration path of lithium ions within the electrode. When the porosity is within the above-mentioned range, the negative electrode active material layer has an appropriate amount of pore structure. On the one hand, it can store enough electrolyte, ensuring sufficient electrolyte supply at the interface between the functional coating and the electrode, and smooth ion transport. On the other hand, it avoids excessive loss of electrolyte adsorbed by the functional coating into the electrode due to excessively high porosity, resulting in reduced solid-phase contact, decreased conductivity, or excessive loss of electrolyte into the electrode. Simultaneously, within the above-mentioned porosity range, graphite particles can form a stable physical network structure during compaction, and the expansion and contraction amplitudes of the negative electrode during cycling are relatively balanced, preventing situations where excessively low porosity leads to excessively rapid accumulation of expansion force or excessively high porosity leads to a loose electrode structure. This porosity range is compatible with the expandable space inside the cell reflected by PM in the formula, so that the expansion force of the cell changes smoothly during cycling, and the functional coating thickness H can play a stable rigid support and liquid retention role under the constraints of the formula.

[0047] In one embodiment of this application, the negative electrode active material layer further includes a second binder, the second binder comprising at least one of styrene-butadiene rubber (SBR), acrylonitrile multi-element copolymer LA133, and polyacrylic acid (PAA); the mass ratio of the negative electrode active material to the second binder is (96%-98%):(0.8%-1.5%). Exemplarily, the mass ratio of the negative electrode active material to the second binder is any one of 96%:1.5%, 98%:1.5%, 96%:1.1%, 98%:1%, 96%:0.8%, 98%:0.8%, or any ratio within the range formed by any pairwise ratios mentioned above.

[0048] The binder provides uniform and moderate adhesion to the graphite particles, enabling the electrode to form a stable orientation structure during the rolling process. This helps to control the orientation index of the negative electrode within a suitable range, ensuring that the expansion behavior of the negative electrode during cycling is consistent with the design expectations. At the same time, the appropriate amount of binder avoids excessive swelling of the binder in the electrolyte, which would increase the expansion force. This allows the thickness H of the functional coating to accurately match the actual expansion degree of the negative electrode under the constraints of the formula, fully leveraging the rigid support and liquid retention functions, and effectively suppressing cycling drop.

[0049] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0050] Example 1 1. Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, conductive agent (conductive carbon black SP), and binder (polyvinylidene fluoride PVDF) are mixed thoroughly in an N-methylpyrrolidone solvent system at a weight ratio of 97%:2%:1%. The mixture is then coated onto a 12μm thick positive current collector aluminum foil, dried, and rolled to obtain the positive electrode sheet.

[0051] 2. Preparation of negative electrode sheet Artificial graphite (median particle size Dv50 of graphite is 12000 nm, orientation index OI = 0.45), conductive agent (conductive carbon black SP), binder (styrene-butadiene rubber SBR), and thickener (sodium carboxymethyl cellulose CMC) were thoroughly mixed in a deionized water solvent system at a weight ratio of 97%:1%:1.2%:0.8%. This mixture was then coated onto a 6 μm thick copper foil used as a negative electrode current collector. After drying and cold pressing, the negative electrode sheet was obtained. The compaction density of the negative electrode active material layer in the negative electrode sheet was 1.60 g / cm³. 3 The porosity is 32%.

[0052] 3. Diaphragm preparation The components (functional material (polyvinyl alcohol PVA, elastic modulus of 11.6 MPa, liquid absorption ratio of 5.2), first binder (polyvinylidene fluoride PVDF), and solvent (N-methylpyrrolidone NMP)) were weighed in a mass ratio of 65%:1%:34%, mixed, and stirred into a homogenous slurry. The resulting slurry was coated onto the surface of a PE membrane substrate and vacuum dried to obtain a membrane with a functional coating. The functional coating was applied to the side of the membrane closest to the negative electrode, and the thickness H of the functional coating was 3.5 μm.

[0053] 4. Electrolyte preparation Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:EMC:DEC = 30:30:40 to obtain an organic solvent; lithium salt LiPF6 was dissolved in the above mixed organic solvent to obtain an electrolyte with a LiPF6 concentration of 1.2M.

[0054] 5. Preparation of secondary batteries The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. This is then wound to obtain a bare cell. The bare cell is placed in a square aluminum casing, injected with the electrolyte, and then encapsulated and formed to obtain a square lithium-ion secondary battery.

[0055] Along the thickness direction of the square aluminum shell, the difference between the inner wall spacing of the square aluminum shell and the thickness of the battery cell is PM = 300μm, with an influence factor a = 2.363 and an influence factor b = 3.457.

[0056] The specific settings of Examples 1-10 and Comparative Examples 1-3 are shown in Table 1-2 below; the other steps and parameter settings in Examples 2-10 and Comparative Examples 1-3 are consistent with those in Example 1.

[0057] Table 1

[0058] Table 2

[0059] Test methods I. Functional Coating Thickness Test After the functional coating is applied, the diaphragm is placed in a Mahr thickness gauge to measure its total thickness. Then, the base membrane is placed in the Mahr thickness gauge to measure its thickness. The functional coating thickness H = the total diaphragm thickness. Base film thickness.

[0060] II. Graphite Orientation Index (OI) Test X-ray diffraction (XRD) was performed on the graphite powder. The test conditions were: Cu target, Kα rays, wavelength λ=1.5406Å, and scanning speed: 2° / min. The diffraction peaks of the (002) and (004) crystal planes were identified based on the obtained diffraction patterns. The peak areas of the two peaks were obtained by integrating the peak areas. The diffraction peak areas of the (002) and (004) crystal planes were calculated as follows: OI = (002) crystal plane diffraction peak area / (004) crystal plane diffraction peak area.

[0061] III. PM Test The thickness of the battery cell is measured directly using a vernier caliper or micrometer and denoted as T. 电芯 ; Use vernier calipers to measure the distance T between two opposite outer walls of the square aluminum shell in the cell stacking direction. 壳体 Subsequently, at least three different locations on the shell were selected, and the shell wall thickness was measured using a micrometer or scanning electron microscope. The average value was recorded as t; the inner wall spacing of the shell = T 壳体 -2×t; PM = (T) 壳体 -2×t)-T 电芯 .

[0062] IV. Functional Material Testing 1. Elastic modulus test The functional material powder was pressed into shape in a mold at a pressure of 10 MPa for 5 minutes to obtain a block sample with dimensions of 100 mm (length) × 100 mm (width) × 10 mm (height). The pressing conditions were such that the sample was intact and free of obvious cracks. At least 5 samples were prepared for each embodiment, and the average value of the test results was taken.

[0063] Under dry atmosphere (23±2℃), place the sample between the upper and lower plates of a universal testing machine or press, ensuring the sample is centered and the pressure surface is flat. Compress the sample uniformly along its height at a speed of 0.1 mm / min, recording the compression displacement and corresponding compressive force. Plot a stress-strain curve (stress = compressive force / sample pressure area, strain = compressive displacement / initial sample height), and take the slope of the initial linear segment of the stress-strain curve as the elastic modulus. The linear segment should be selected within the range of 0.1%–0.5% of the strain.

[0064] 2. Liquid absorption ratio test 1 kg of functional material was immersed in an electrolyte (LiPF6 concentration of 1.2 M, and the solvent in the electrolyte was a mixture of raw materials with a mass ratio of EC:EMC:DEC = 30:30:40) until the functional material was completely submerged. After 24 hours, the material was removed, drained, and weighed. The liquid absorption ratio was calculated as follows: (weight of functional material after immersion) / (weight of functional material after immersion). (Initial weight of functional materials) / Initial weight of functional materials.

[0065] V. Compacted density test Use a sampler to punch at least three samples with an area of ​​1540.25 mm² at different locations (such as the head, middle, and tail) on the negative electrode sheet. 2 The electrodes of the circular plates were measured using a micrometer, and the total electrode thickness h1 of each plate was measured. The active material layer on the surface of each plate was then removed using a solvent or by scraping with a blade to obtain the current collector. The thickness h0 of the current collector was measured, and the difference between the two is the coating thickness h = h1 - h0. The mass m1 of each plate and the mass m0 of the current collector were weighed using an analytical balance. The mass m of the active material layer is m = m1 - m0, and the surface density is m / S (where S is the area of ​​the plate, S = 1540.25 mm²). 2 Compacted density = surface density / h, taking the average value of the test results from each sampling point. The unit is g / cm3.

[0066] VI. Porosity Test of Negative Electrode Active Material Layer The porosity ε of the negative electrode sheet was obtained by the mass difference method. The electrode sheet was cut into circular sheets with a radius r of 0.95 cm using an electrode sheet punching machine, and the thickness L of the electrode sheet and the thickness L0 of the current collector were measured using a thickness gauge. The volume of the negative electrode active material on the cut electrode sheet was calculated as V = π × r. 2×(L-L0); Weigh the cut electrode sheet using a balance with an accuracy of 0.0001g and record the mass as m1. Then soak the electrode sheet in hexadecane for 1 hour (completely immersed in it). Remove the electrode sheet with tweezers and blot it dry with filter paper until the mass is constant. Weigh it using a balance and record the mass as m2. Substituting the experimental data into the formula, we can calculate: ε = (m2 - m1) / (V × ρ) × 100%, where ρ is the density of hexadecane, 0.7734 g / cm³. 3 .

[0067] VII. Cyclic Diving Test The batteries of the above-described embodiments and comparative examples were cycled according to the following procedure: The battery cells were constrained on both sides with aluminum plates with a constraining force of 300 kgf; the battery cells were charged at a constant current of 1C to 4.2V, then charged at a constant voltage of 4.2V to the cutoff current of 0.05C, and left to stand for 60 minutes; then discharged at a constant current of 1C to 2.8V, and left to stand for 60 minutes, and cycled until the capacity retention rate was 80%.

[0068] Record the discharge capacity for each cycle. Using the discharge capacity of the first cycle as a baseline, calculate the capacity retention rate for each cycle (capacity retention rate = discharge capacity of the current cycle / discharge capacity of the first cycle × 100%). Plot the capacity decay curve with the number of cycles on the x-axis and the capacity retention rate on the y-axis. Perform linear fitting on the data points on the curve; the slope of the fitted line is K.

[0069] Judgment criteria: A slope K ≤ -1 on the capacity decay curve indicates that a cyclic drop has occurred; a slope K > -1 on the capacity decay curve indicates that a cyclic drop has not occurred.

[0070] Based on Example 1, Comparative Example 1, and Tables 1-2, it can be seen that in Comparative Example 1, the separator surface is not coated with a functional coating, and the slope K value of the corresponding capacity decay curve is -1.6, indicating a severe capacity drop during cycling. This is because, without a functional coating, the separator itself lacks sufficient rigid support and electrolyte retention capacity. During the later stages of cycling, as the internal expansion force of the cell increases, the electrolyte in the separator pores is directly squeezed out, leading to obstructed ion transport and rapid capacity decay.

[0071] Based on Example 1, Comparative Example 2, and Tables 1-2, it can be seen that in Comparative Example 2, the orientation index (OI) of the graphite negative electrode active material is 0.62, and the thickness of the functional coating is 2.5 μm. Although the functional material itself meets the requirements of high elastic modulus and high liquid absorption ratio, the calculated value obtained by substituting the above parameters into the formula is 3.79 μm. At this time, the thickness of the functional coating is 3.5 μm, which is less than the calculated value and does not meet the requirements of the formula. The capacity decay curve slope K of the battery corresponding to Comparative Example 2 is -1.40, indicating a rapid capacity drop. This is because when the thickness of the functional coating is insufficient to resist the extrusion force generated by the current expansion of the negative electrode and the internal space conditions of the cell, the coating cannot maintain sufficient pore structure and electrolyte retention after being compressed. The electrolyte in the separator will still be squeezed out, leading to a rapid capacity drop. Therefore, even if the functional material itself has sufficient elastic modulus and liquid absorption ratio, if the functional coating thickness H does not satisfy the formula H≥(a×OI)×(b×PM) / 400, that is, if the functional coating thickness is insufficient to resist the extrusion force generated by the expansion of the negative electrode and the internal space conditions of the cell, it still cannot effectively suppress the battery's cycle drop.

[0072] Based on Example 1, Comparative Example 3, and Tables 1-2, it can be seen that the functional material used in the functional coating of Comparative Example 3 is polyoxyalkyleneamine (POA). This material has an elastic modulus of only 5.8 MPa (<10 MPa) and a liquid absorption ratio of only 1.2 (<3.5), both of which do not meet the relevant limitations for functional materials. Although the thickness H of the functional coating meets the formula requirements, the results show that the slope K of the capacity decay curve of the battery in Comparative Example 3 is -1.80, indicating a significant drop in capacity over time. Furthermore, the K value is the smallest among all comparative examples, indicating the most severe capacity decay. This is because when the elastic modulus of the functional material is too low, the coating cannot maintain rigidity under pressure, resulting in collapse and deformation, and the pore structure is destroyed. Conversely, when the liquid absorption ratio is too low, the amount of electrolyte adsorbed and retained by the coating itself is insufficient, failing to provide effective electrolyte replenishment when the membrane pores are under pressure. Under the above circumstances, even if the thickness of the functional coating meets the formula limit, the functional material itself lacks sufficient rigidity and liquid absorption and retention capacity. Therefore, the functional coating still cannot maintain the pore structure of the separator and the supply of electrolyte under pressure, and thus cannot effectively suppress the battery cycle drop.

[0073] Combining Examples 1-2 and Table 1, it can be seen that in Example 2, the functional material was replaced by polyacrylamide (elastic modulus of 10.2 MPa, liquid absorption ratio of 4.8) instead of polyvinyl alcohol in Example 1. Although the elastic modulus and liquid absorption ratio of the functional material were lower than those in Example 1, they remained above 10 MPa and 3.5, respectively. Simultaneously, the coating thickness H = 3.5 μm met the formula requirements, therefore, the battery did not experience cycle failure. This indicates that using polyvinyl alcohol or polyacrylamide as the functional material, as long as its elastic modulus and liquid absorption ratio reach the above levels and the coating thickness meets the formula requirements, cycle failure can be effectively suppressed.

[0074] Combining Examples 1, 3-4 and Table 1-2, it can be seen that when the orientation index OI of the negative electrode active material graphite changes, Examples 1 and 3-4 both satisfy the matching relationship defined by H≥(a×OI)×(b×PM) / 400, and the slope K value of their capacity decay curves is greater than -1, and no cyclic drop occurs. This indicates that under this matching relationship, the change of OI within a certain range will not affect the achievement of the effect of suppressing cyclic drop.

[0075] Combining Examples 1, 5-6 and Table 1-2, it can be seen that when the expandable space PM inside the cell changes, Examples 1 and 5-6 both satisfy the matching relationship defined by the formula H≥(a×OI)×(b×PM) / 400, and the slope K value of their capacity decay curves is greater than -1, and no cyclic dripping occurs. This indicates that under this matching relationship, changes in PM within a certain range will not affect the achievement of the effect of suppressing cyclic dripping.

[0076] Combining Examples 1, 7-8, and Table 1-2, it can be seen that when the orientation index (OI) of the negative electrode active material graphite further changes, H in Examples 1 and 7-8 all satisfy the matching relationship defined by H ≥ (a × OI) × (b × PM) / 400, and the slope K value of their capacity decay curves is greater than -1, indicating that no cyclic degradation occurs. Based on the conclusions of Examples 3-4 above, under different OI values, as long as H satisfies this matching relationship, the effect of suppressing cyclic degradation can be achieved, indicating that this matching relationship has good applicability and stability when the OI value changes.

[0077] Combining Examples 1, 9-10, and Table 1-2, it can be seen that the compaction density and porosity of the negative electrode active material layer were adjusted to 1.65 g / cm³. 3 and 25%, 1.50g / cm 3When the compaction density and porosity of the negative electrode active material layer change at 40%, the matching relationship defined by H ≥ (a×OI)×(b×PM) / 400 is satisfied in Examples 1 and 9-10. The slope K value of their capacity decay curves is greater than -1, and no cyclic drop occurs. This shows that under different electrode structure conditions, as long as H satisfies this matching relationship, the effect of suppressing cyclic drop can also be achieved. The applicability of this matching relationship does not depend on specific electrode compaction density and porosity conditions.

[0078] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application, but such modifications or substitutions are all within the scope of protection of this application.

Claims

1. A secondary battery, characterized in that: The device includes a housing and a battery cell disposed within the housing, the battery cell comprising a positive electrode, a negative electrode, and a separator; The negative electrode sheet includes a negative current collector and a negative active material layer. The negative active material layer includes a negative active material, which includes graphite. The orientation index of the graphite is denoted as OI. The diaphragm has a functional coating disposed on at least one side surface along its thickness direction, the thickness of the functional coating being denoted as H μm; the functional coating comprises a functional material, the elastic modulus of the functional material being ≥10MPa and the liquid absorption ratio of the functional material being ≥3.5; Along the thickness direction of the housing, the difference between the inner wall spacing of the housing and the thickness of the battery cell is denoted as PM μm; The OI, the H, and the PM satisfy the following relationship: H≥(a×OI)×(b×PM) / 400; Wherein, 'a' is the first influence factor and 'b' is the second influence factor; the value range of 'a' is 2.3 ≤ a ≤ 2.5 and the value range of 'b' is 3.2 ≤ b ≤ 3.

6.

2. The secondary battery as described in claim 1, characterized in that: The OI, the H, and the PM satisfy at least one of the following conditions: (1) The value of OI is 0.3-0.7; (2) The value of H is 2.5-5.0; (3) The value of PM is 100-500.

3. The secondary battery as described in claim 1, characterized in that: The functional material includes at least one of polyacrylamide, polyvinyl alcohol, polyoxyethylene, and polyacrylic acid.

4. The secondary battery as described in claim 1, characterized in that: The functional coating also includes a first adhesive, which includes at least one of polyvinylidene fluoride, polyoxyalkyleneamine, and polymethyl methacrylate.

5. The secondary battery as described in claim 4, characterized in that: The mass ratio of the functional material to the first adhesive is (80-95):(0.1-1).

6. The secondary battery as described in claim 1, characterized in that: The functional coating is applied to the surface of the diaphragm near the negative electrode sheet.

7. The secondary battery as described in claim 1, characterized in that: The median particle size Dv50 of the graphite is between 10000nm and 13000nm.

8. The secondary battery as described in claim 1, characterized in that: The compaction density of the negative electrode active material layer is 1.5-1.65 g / cm³. 3 .

9. The secondary battery as described in claim 1, characterized in that: The porosity of the negative electrode active material layer is 25%-40%.

10. The secondary battery as described in claim 1, characterized in that: The negative electrode active material layer further includes a second binder, which includes at least one of styrene-butadiene rubber, acrylonitrile copolymer, and polyacrylic acid. The mass ratio of the negative electrode active material to the second binder is (96%-98%): (0.8%-1.5%).